2012
DOI: 10.4103/0253-7184.102128
|View full text |Cite
|
Sign up to set email alerts
|

Rare sweat gland tumors of vulva: Report of two cases

Abstract: Syringomas and Fox–Fordyce disease are appendageal skin disorders. While syringomas represent an adenoma of the intraepidermal eccrine duct, Fox Fordyce disease occurs due to blockage of the apocrine sweat duct. In both conditions, extragenital sites are more frequently involved than the genitalia. We herein report two young females, one with syringomas on the face and vulva and the other with Fox Fordyce disease involving axilla, areola and vulva, thereby citing the importance of examination of genitalia in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…. Vulvar syringoma is a relatively rare occurrence, with only few cases reported in the literature to date [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…. Vulvar syringoma is a relatively rare occurrence, with only few cases reported in the literature to date [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, skin near the affected area may become darkened, and hair may become sparse in the affected areas. [1] Apocrine anhidrosis may result eventually.…”
Section: Discussionmentioning
confidence: 99%
“…Initially described as lymphangiomas by Kaposi and Biesiadeki (1872), syringomas have since been recognized as adnexal in origin—specifically, as benign tumors of the eccrine sweat glands ( Mahajan et al., 2012 ). Although most commonly seen on the face and neck of young women, vulvar syringomas have also been described on the labia majora, typically appearing as multiple 1- to 4-mm, firm, skin-colored to brownish-pink papules in a symmetric, bilateral distribution ( Fig.…”
Section: Benign Neoplasmsmentioning
confidence: 99%
“…These lesions are usually asymptomatic and diagnosed incidentally during routine examination; however, pruritus can be a complaint, with some patients experiencing exacerbations during menstruation or warmer months ( Gerdsen et al., 2002 ; Huang et al., 2003 ). Syringomas often arise during puberty and enlarge during pregnancy and with the use of oral contraceptives ( Mahajan et al., 2012 ). It has therefore been suggested that the growth of syringomas is hormonally influenced, although the literature has remained inconclusive to date ( Huang et al., 2003 ).…”
Section: Benign Neoplasmsmentioning
confidence: 99%
See 1 more Smart Citation